Distributed Cooperative Synchronization Control Of 2 Articulated Robots For Industry 4.0 Application - Md Hanif, Mohamad Norhafifi (Universiti Sains Malaysia, 2018)
This project present on the design of distributed cooperative synchronization between master unit and slave unit. Within this project, two slave robot arms is connected over a network which the control signal of it will likely be share throughout and the data about every robot is exchange amongst them. Cooperation and interconnected of the shared signal concept in series of robot arms to aim for same goal bring the spirit of industry 4.0. The system contains 3 parts which are control design, hardware environment and software environment. The master arm unit will interface with both slave unit by using Arduino Mega 2560 microcontroller. As it is distributed system, 2 Arduino Mega 2560 is used as different brain to control the slave robot arms. It also used to cooperate with MATLAB as all the command or block diagram to control the synchronization between master and both slave units comes from it. It is target to be implement in cooperative, remote or hazardous surroundings. To achieve excellent synchronization, phase lead compensated control is used to let the robot arms to move in accurate motion in the same manner between the interaction of master feedback unit and both slave robot arms as the position error is reduced. The controlled system performance was measured by using Integral Absolute Error (IAE) to observe the synchronization accuracy.